Evaluation of Mechanical Characteristics based on Tool Pin Shapes in Friction Stir Welding of A6061-T6 - Kim, Dae-Hwan; Lim, Byung-Chul; Lee, Han-Seop; Park, Sang-Heup (International Journal of Engineering and Technology, 2019)
Using 6061-T6 alloy sheets, which are high-strength age-hardening materials used in automobile parts, an analysis of the strength characteristics and integrity of welding joints was performed based on the changes in welding conditions such as rotation direction, stirring rate, and welding speed that are in turn dependent on the rotating tool pin during friction stir welding (FSW). Regarding the exterior of FSW specimens, which were fabricated by using rotating tools having A and B type pins, the joint formed when the tool shoulder rotates appeared on the overall friction welded surface of each specimen, regardless of the tool pin shape or welding state; pores or non-welded zones did not form. In other words, by observing the FSW specimens, satisfactory exteriors were found in general in all FSW conditions. As part of mechanical property evaluation, the maximum tensile strength measured was 199.1 MPa for the A type pin welding speed of 300 mm/min and rotation rate 3,000 rpm; the tensile strength of the A type pin was higher than that of the B type pin. As a result of measuring the microhardness, the distribution of hardness values were Hv104 and Hv111 in the case of 400 mm/min welding speed and 3,000 rpm tool rotation rate for the A type and B type pins, respectively, and Hv48 and Hv50, respectively, in the case of 200 mm/min welding speed and 2,000 rpm tool rotation rate. Observing the microstructures by using an optical microscope, the effect of pin type on microstructure was small; the stir zone was fine and uniform since plastic deformation occurred due to the rotation of the pin. In the thermal-mechanically affected zone, plastic deformation and partial recrystallization were observed. In the heat-affected zone, grains became coarse due to the heat produced during FSW.Â Â